Leaching characteristic of red gypsum under column and oedometric conditions - Noor Hidayah, Mohd Hazari (2019)
Red gypsum (RG) is a by-product produced during the extraction of titanium dioxide (TiO2) from ilmenite ores. Unregulated and rampant disposal activity of RG might be an issued due to waste gypsum arising from chemical industry or power plant annually without being utilize. The leachability of heavy metals of this waste will be leach into the soil groundwater. The main objective of this study is to determine the leaching characteristics of RG under Column and Oedometric conditions and comparing the concentration of elements with Toxicity Characteristic Leaching Procedure (TCLP), Total Threshold Limit Concentration (TTLC) and Drinking Water Quality Standards (NDWQS). The concentrations and types of heavy metals were analyzed using the Inductively Coupled Plasma Mass Spectrometry (ICP-MS) method. Experimental results demonstrated that only a few of the major elements that are traced from both leaching tests carried out by Column leaching test and Oedometer leaching test such as Mg, Ca, Na, Al and K. The highest concentration of major element is Mg (129.5 mg/L). In addition, some of heavy metals produced are Mn, Ni, Cu, Zn and Pb. The highest concentration of these five heavy metals is Zn (0.031 mg/L). However, the value of this concentration still does not exceed the limits provides in TTLC and NDWQS with the value of 5000 mg/L and 3 mg/L respectively. The results recorded element concentration under Column leaching test were higher than Oedometer leaching test. Overall, all element concentrations of RG were found to all relevant consideration standards of TCLP, TTLC and NDWQS as the elements that leach out were found to be less than allowable limits.